A high coercive force magnet and its preparation method

Magnetic powder is prepared by mixing and smelting of material A and material B, and the Nd2Fe14B main phase is formed by using elements such as praseodymium and neodymium alloy, and the crystals are refined through diffusion and permeation of elements such as M, Si, and Cr, and the existing neodymium iron boron is solved. The problem of insufficient coercive force of magnets has achieved the improvement of high coercive force and comprehensive magnetic performance.

CN115458267BActive Publication Date: 2025-02-11CIXI XINGFA MAGNETIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211178455.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-26
Publication Date
2025-02-11
Estimated Expiration
2042-09-26

AI Technical Summary

Technical Problem

When existing neodymium iron boron magnets increase coercive force, they can easily lead to reverse parallel arrangement of magnetic moments, reduce residual magnetic and magnetic energy production, and Dy elements are expensive.

Method used

The magnet powder is prepared by mixing and smelting of material A and material B. The praseodymium-neodymium alloy, gadolinium-ferroalloy and boron-ferroalloy in material A form the Nd2Fe14B main phase at high temperature, and the elements such as M, Si, Cr in material B are in the liquid phase. Diffusion and permeation, replace Nd, refine grains, and enhance coercivity.

Benefits of technology

It significantly improves the coercive force and comprehensive magnetic properties of the magnet, reduces abnormal grain growth, and improves grain size uniformity, making it suitable for special industrial application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003864355140000101
    Figure BDA0003864355140000101
Patent Text Reader

Abstract

The present application relates to the technical field of neodymium iron boron magnets, and specifically discloses a high coercive force magnet and a preparation method thereof. A high coercive force magnet is mainly made of the following raw materials in parts by weight: 53-68 parts of material A, 1.9-2.6 parts of material B, and 0.55-0.82 parts of auxiliary materials; the material A includes the following components: praseodymium-neodymium alloy, gadolinium-iron alloy, boron-iron alloy, cerium, copper, aluminum, zirconium, titanium, and cobalt; the balance is iron and other inevitable impurities; the material B includes the following components in mass percentage: M: 23.6-30.2%; Si: 0.12-0.35%; Cr: 0.1-0.25%; the balance is iron and other inevitable impurities; the M is at least one of Mn, In, Ag, Mg, Y, La, Ce, and Sc. The high coercive force magnet of the present application has the advantages of high coercive force and good comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of neodymium iron boron magnets, and more specifically, to a high coercive force magnet and a preparation method thereof. Background Art

[0002] Neodymium magnets, also known as NdFeB magnets, are made of neodymium, iron, and boron (Nd2Fe 14 B) tetragonal crystals are formed, and in order to further improve the magnetic properties of NdFeB, other elements are usually added to the ternary Nd-Fe-B material. The elements enter the matrix phase in the form of doping or substitution, which can improve the magnetic properties of the main phase.

[0003] With the continuous development of domestic NdFeB magnet production technology, and the rapid expansion of other emerging industries such as computer industry, information industry, communication industry, automobile industry, etc., the output and demand of NdFeB magnets have gradually increased sharply. However, at the same time, there are higher requirements for the performance of NdFeB magnet materials, such as temperature stability, coercive force and other properties need to be further improved.

[0004] The Chinese patent application document with application publication number CN104064301A discloses a neodymium iron boron magnet and a preparation method thereof, which comprises, by mass percentage, Pr-Nd: 29% to 33%, B: 0.97% to 1.5%, Dy: 0.4% to 0.6%, Al: 0.2% to 0.8%, Co: 0.6% to 0.8%, Cu: 0.01% to 0.5%, Zr: 0.01% to 0.2%, and the remainder is Fe. A certain amount of Dy is added to refine the magnet grains to improve the coercive force of the magnet.

[0005] For the above-mentioned NdFeB magnets, although adding some Dy, Zr and other elements into the main phase can improve the coercive force to a certain extent, the Dy element is expensive and adding a certain amount will also cause the magnetic moment to be arranged in an anti-parallel manner, resulting in a decrease in the remanence and magnetic energy product of the magnet. Summary of the invention

[0006] In order to improve the comprehensive magnetic properties of a magnet, the present application provides a high coercive force magnet and a preparation method thereof.

[0007] In a first aspect, the present application provides a high coercive force magnet, which adopts the following technical solution:

[0008] A high coercive force magnet is mainly made of the following raw materials in parts by weight: 53-68 parts of material A, 1.9-2.6 parts of material B, and 0.55-0.82 parts of auxiliary materials;

[0009] The material A includes the following components in percentage by mass:

[0010] Neodymium-praseodymium alloy 15-25.5%;

[0011] Gadolinium iron alloy 1.5-2%;

[0012] Ferroboron alloy 0.5-1.2%;

[0013] Cerium 7-12%;

[0014] Copper 0.1-0.3%;

[0015] Aluminum 0.25-0.5%;

[0016] Zirconium 0.2-0.35%;

[0017] Titanium 0.1-0.18%;

[0018] Cobalt 0.25-0.45%;

[0019] The balance is iron and other unavoidable impurities;

[0020] The material B includes the following components in percentage by mass:

[0021] M: 23.6-30.2%;

[0022] Si: 0.12-0.35%;

[0023] Cr: 0.1-0.25%;

[0024] The balance is iron and other inevitable impurities; the M is at least one of Mn, In, Ag, Mg, Y, La, Ce, and Sc.

[0025] By adopting the above technical solution, material A and material B are mixed and smelted to obtain magnet powder. The praseodymium-neodymium alloy, gadolinium-iron alloy and boron-iron alloy in material A are melted at high temperature to form Nd2Fe 14 For the main phase B, on the one hand, the Nd-rich phase is evenly distributed at the junction of the main phase grains, which greatly improves the coercive force of the magnet. On the other hand, the elements such as M, Si, Cr in material B flow and penetrate into the grain boundaries of the main phase after melting. Some elements replace Nd, further improving the coercive force, and the other elements are evenly distributed around the main phase grains, which plays a role in isolating exchange coupling, improving the coercive force of the magnet and playing a role in liquid phase sintering. At the same time, there will be more Nd-rich liquid phases, which will dissolve the protrusions and edges of fine powder particles or large particles in the liquid phase, and then inhibit grain growth within a suitable range. Refining the grains reduces the defect density of the T1 phase interface, reduces the nucleation of the reverse magnetization domain at the interface, and greatly improves the coercive force of the magnet while maintaining other properties.

[0026] Preferably, the mass ratio of material A to material B is (20-41):1.

[0027] By adopting the above technical solution, the mass ratio of material A to material B is optimized and adjusted. Although the addition of multiple non-magnetic metal elements in material B will increase the coercive force, excessive addition will lead to a decrease in the Br and (BH)max of the magnet. This application selects a suitable addition ratio to improve the coercive force while ensuring other properties of the magnet.

[0028] Preferably, the average particle size of the material A and the material B is 5-10 μm.

[0029] By adopting the above technical scheme, the average particle size of material A and material B after powdering is tested and adjusted so that the fine particles of material A and material B have a more appropriate surface area, and the grain refinement of the magnet is improved while ensuring the low oxidation state of the Nd-rich phase, which is conducive to the production of strip-shaped Nd-rich phase, so that more main phase grains are wrapped, thereby isolating the magnetic exchange coupling between the main phases.

[0030] Preferably, the auxiliary material consists of a metallocene and an antioxidant in a molar ratio of (0.55-0.75):1.

[0031] By adopting the above technical solution, since material A and material B have a large surface area after powdering and are very easy to oxidize, the addition of metallocene and antioxidant can reduce the impact of oxygen on the material during the powdering process. At the same time, the addition of metallocene can introduce a suitable amount of unsaturated bonds, and due to its own rigid structure, it can fully combine with the corresponding active sites, play a good protective role for Nd atoms in a high-energy state, reduce the damage of oxygen atoms to the crystal phase structure, and further improve the comprehensive performance of the magnet such as coercive force.

[0032] Preferably, the metallocene is at least one of ferrocene, manganocene, zirconocene dichloro, and titanocene dichloro.

[0033] By adopting the above technical solution, the type composition of metallocene is optimized and adjusted, the active state and steric hindrance of metallocene are balanced, the crystal phase state of the magnet is further improved, and the coercive force is enhanced.

[0034] Preferably, the antioxidant is one of tert-butylhydroquinone and antimony dialkyl dithiocarbamate.

[0035] By adopting the above technical solution, tert-butylhydroquinone, antimony dialkyl dithiocarbamate and metallocene have a better compounding effect, further improving the magnetic properties of the magnet.

[0036] In a second aspect, the present application provides a method for preparing a high coercive force magnet, using the following technical solution: A method for preparing a high coercive force magnet, comprising the following steps:

[0037] S1: Smelting: according to the formula of material A, praseodymium-neodymium alloy, gadolinium-iron alloy, boron-iron alloy, cerium, copper, aluminum, zirconium, titanium, cobalt and the remaining components are measured and mixed evenly for smelting to obtain smelting material A;

[0038] According to the formula of material B, M, Si, Cr and the remaining components are mixed evenly and smelted to obtain smelting material B;

[0039] S2: Powder making: hydrogen-crushing the smelting material A and the smelting material B to obtain a coarse powder; then the coarse powder and the auxiliary materials are mixed together and jet-milled to obtain a fine powder;

[0040] S3: Molding: The fine powder is filled, oriented and pressed in a mold to obtain a green body;

[0041] S4: Sintering: Dehydrogenate, sinter and temper the green body to obtain a semi-finished product;

[0042] S5: Grinding: The semi-finished product is obtained by grinding.

[0043] By adopting the above technical scheme, material A and material B are smelted separately, and then subjected to hydrogen crushing, uniform stirring and mixing, and fine grinding to obtain fine powder with uniform particle size, and then oriented, pressed, and sintered to obtain a magnet product with higher coercive force and better comprehensive magnetic properties.

[0044] The magnets of the present application can be changed in size according to customer needs, including but not limited to cylindrical, square, tile, special-shaped and other shapes.

[0045] Preferably, in step S4, the sintering is performed at 830-900°C in vacuum for 0.5-1h, followed by sintering at 1050-1150°C in vacuum for 1.5-2h, and then keeping at 1150-1250°C for 1-1.5h.

[0046] By adopting the above technical scheme, the impurity components such as water vapor, hydrogen, nitrogen, organic matter, etc. in the magnetic powder are first volatilized and removed rapidly at a relatively low temperature to ensure the purity of the magnetic powder. Then, after secondary sintering, the sharp edges and protruding parts of the main phase grains are promoted to be dissolved by the liquid phase, further refining the grains and improving the coercive force of the magnet.

[0047] Preferably, in step S4, the tempering is performed by air cooling to 60-80°C and keeping it for 1-3 minutes, then rapidly heating to 850-900°C and keeping it for 1.5-2 hours, and then cooling to 500-600°C and keeping it for 1-1.5 hours.

[0048] By adopting the above technical solution and the special process of air cooling plus two tempering, the average grain size of the main phase can be effectively reduced, while reducing the area of ​​the low anisotropy region inside the main phase grains or the outer layer of the grains, so that the main phase grains are more fully surrounded by the Nd-rich grain boundary phase, thereby weakening the magnetic interaction between the main phase grains and further improving the coercive force of the magnet.

[0049] In summary, this application has the following beneficial effects:

[0050] 1. Since the present application adopts a mixture of material A and material B, the diffusion and penetration of elements in material B in the liquid phase are utilized to suppress the generation of large grains, refine the grains of the magnet, and improve the coercive force and comprehensive performance of the magnet.

[0051] 2. In the present application, suitable sintering temperature and tempering temperature are preferably used to further reduce the probability of large grains swallowing small grains during the production process, reduce abnormal grain growth, improve the uniformity of grain size in the magnet, and thus increase the coercive force.

[0052] 3. The high coercive force magnet prepared by the preparation method of the present application has good comprehensive magnetic properties, especially high coercive force, and is suitable for special industrial application scenarios. DETAILED DESCRIPTION

[0053] The present application is further described in detail below in conjunction with embodiments.

[0054] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0055] Example

[0056] Example 1

[0057] The high coercive force magnet of this embodiment is made of the following raw materials in parts by weight: 5.3 kg of material A, 0.26 kg of material B, and 0.055 kg of auxiliary materials.

[0058] Among them, material A includes the following components in percentage by mass: 15% praseodymium-neodymium alloy, 2% gadolinium-iron alloy, 0.5% ferroboron alloy, 12% cerium, 0.1% copper, 0.25% aluminum, 0.35% zirconium, 0.1% titanium, and 0.25% cobalt; the remainder is iron and other inevitable impurities.

[0059] Material B includes the following components in mass percentage: M: 23.6%, Si: 0.35%, Cr: 0.1%; the balance is iron and other inevitable impurities; M is composed of In, Y, and La in a molar ratio of 0.35:0.6:1.

[0060] The auxiliary material is boron carbide.

[0061] The method for preparing the high coercive force magnet of this embodiment comprises the following steps:

[0062] S1: Melting: according to the formula of material A, praseodymium-neodymium alloy, gadolinium-iron alloy, boron-iron alloy, cerium, copper, aluminum, zirconium, titanium, cobalt and the remaining components are measured and put into a medium frequency induction melting furnace for melting, and the raw materials are put in the following order: boron-iron alloy is put in the center of the bottom of the furnace, pure iron is placed along the inner wall of the furnace, and the other refractory metal raw materials are placed in the middle and lower part, and the melting material A is obtained after melting;

[0063] According to the adding method of material A, M, Si, Cr and the remaining components are taken according to the formula of material B and added into the furnace for smelting to obtain smelting material B; the smelting temperature is not less than 1500°C;

[0064] S2: Powder making: After the smelting materials A and B are roughly crushed, they are placed in a hydrogen crushing furnace and vacuumized to 10 -3 Pa, hydrogen is introduced for hydrogen cracking to obtain coarse powder, and the hydrogen pressure is set to 0.35Mpa;

[0065] Then the coarse powder, auxiliary materials and lubricant are stirred together, and fine powder is obtained after jet milling under nitrogen protection. The average particle size of the fine powder is 15 μm; the lubricant includes the following components in mass percentage: 90% methanol gasoline, 2% isopropanol, and 8% stearic acid glyceryl;

[0066] S3: Molding: The fine powder is loaded into the mold of the magnetic field molding press, an external magnetic field of 2T is applied for orientation, and then pressed and isostatically pressed to obtain a green body;

[0067] S4: Sintering: The green body is kept at 380°C for 0.5h to remove impurities such as water vapor, hydrogen, carbon dioxide, nitrogen and organic components, then sintered at 650°C for 0.5h, then sintered at 1050°C for 2h, and finally tempered at 600°C for 3h to obtain a semi-finished product;

[0068] S5: Grinding: The semi-finished product is ground by electric spark wire cutting and centerless grinding. The magnet product obtained in this embodiment has a specification of φ10mm×5mm cylinder.

[0069] Example 2

[0070] The high coercive force magnet of this embodiment is made of the following raw materials in parts by weight: 6.8 kg of material A, 0.19 kg of material B, and 0.082 kg of auxiliary materials.

[0071] Among them, material A includes the following components in mass percentage: 25.5% praseodymium-neodymium alloy, 1.5% gadolinium-iron alloy, 1.2% ferroboron alloy, 7% cerium, 0.3% copper, 0.5% aluminum, 0.2% zirconium, 0.18% titanium, and 0.45% cobalt; the remainder is iron and other inevitable impurities.

[0072] Material B includes the following components in mass percentage: M: 30.2%, Si: 0.12%, Cr: 0.25%; the balance is iron and other inevitable impurities; M is composed of Mn, Ag, Ce, Sc in a molar ratio of 2:0.12:0.02:0.05.

[0073] The auxiliary material is tungsten carbide.

[0074] The method for preparing the high coercive force magnet of this embodiment comprises the following steps:

[0075] S1: Melting: according to the formula of material A, praseodymium-neodymium alloy, gadolinium-iron alloy, boron-iron alloy, cerium, copper, aluminum, zirconium, titanium, cobalt and the remaining components are measured and put into a medium frequency induction melting furnace for melting, and the raw materials are put in the following order: boron-iron alloy is put in the center of the bottom of the furnace, pure iron is placed along the inner wall of the furnace, and the other refractory metal raw materials are placed in the middle and lower part, and the melting material A is obtained after melting;

[0076] According to the adding method of material A, M, Si, Cr and the remaining components are taken according to the formula of material B and added into the furnace for smelting to obtain smelting material B; the smelting temperature is not less than 1500°C;

[0077] S2: Powder making: After the smelting materials A and B are roughly crushed, they are placed in a hydrogen crushing furnace and vacuumized to 10 -3 Pa, hydrogen is introduced for hydrogen cracking to obtain coarse powder, and the hydrogen pressure is set to 0.35Mpa;

[0078] Then the coarse powder, auxiliary materials and lubricant are stirred together, and fine powder is obtained after jet milling under nitrogen protection. The average particle size of the fine powder is 15 μm; the lubricant includes the following components in mass percentage: 90% methanol gasoline, 2% isopropanol, and 8% stearic acid glyceryl;

[0079] S3: Molding: The fine powder is loaded into the mold of the magnetic field molding press, an external magnetic field of 2T is applied for orientation, and then pressed and isostatically pressed to obtain a green body;

[0080] S4: Sintering: The green body is kept at 400°C for 0.5h to remove impurities such as water vapor, hydrogen, carbon dioxide, nitrogen and organic components, and then sintered at 900°C for 0.5h, followed by vacuum sintering at 1050°C for 2h, and then kept at 1250°C for 1h;

[0081] Finally, the mixture was cooled to 80°C and kept for 1 minute, then rapidly heated to 850°C and kept for 2 hours, and then cooled to 500°C and kept for 1.5 hours to obtain a semi-finished product.

[0082] S5: Grinding: The semi-finished product is ground by electric spark wire cutting and centerless grinding. The magnet product obtained in this embodiment has a specification of φ10mm×5mm cylinder.

[0083] Example 3

[0084] The high coercive force magnet of this embodiment is made of the following raw materials in parts by weight: 6.2 kg of material A, 0.15 kg of material B, and 0.06 kg of auxiliary material.

[0085] Among them, material A includes the following components in mass percentage: 20.9% of praseodymium-neodymium alloy, 1.65% of gadolinium-iron alloy, 1% of ferroboron alloy, 8.6% of cerium, 0.2% of copper, 0.4% of aluminum, 0.29% of zirconium, 0.15% of titanium, and 0.3% of cobalt; the remainder is iron and other inevitable impurities.

[0086] Material B includes the following components in mass percentage: M: 28.5%, Si: 0.26%, Cr: 0.18%; the balance is iron and other inevitable impurities; M is composed of In, Mn, Y, and La in a molar ratio of 0.62:1.5:0.035:0.012.

[0087] The auxiliary material is titanium carbide.

[0088] The method for preparing the high coercive force magnet of this embodiment comprises the following steps:

[0089] S1: Melting: according to the formula of material A, praseodymium-neodymium alloy, gadolinium-iron alloy, boron-iron alloy, cerium, copper, aluminum, zirconium, titanium, cobalt and the remaining components are measured and put into a medium frequency induction melting furnace for melting, and the raw materials are put in the following order: boron-iron alloy is put in the center of the bottom of the furnace, pure iron is placed along the inner wall of the furnace, and the other refractory metal raw materials are placed in the middle and lower part, and the melting material A is obtained after melting;

[0090] According to the adding method of material A, M, Si, Cr and the remaining components are taken according to the formula of material B and added into the furnace for smelting to obtain smelting material B; the smelting temperature is not less than 1500°C;

[0091] S2: Powder making: After the smelting materials A and B are roughly crushed, they are placed in a hydrogen crushing furnace and vacuumized to 10 -3 Pa, hydrogen is introduced for hydrogen cracking to obtain coarse powder, and the hydrogen pressure is set to 0.35Mpa;

[0092] Then the coarse powder, auxiliary materials and lubricant are stirred together, and fine powder is obtained after jet milling under nitrogen protection. The average particle size of the fine powder is 15 μm; the lubricant includes the following components in mass percentage: 90% methanol gasoline, 2% isopropanol, and 8% stearic acid glyceryl;

[0093] S3: Molding: The fine powder is loaded into the mold of the magnetic field molding press, an external magnetic field of 2T is applied for orientation, and then pressed and isostatically pressed to obtain a green body;

[0094] S4: Sintering: The green body is kept at 400°C for 0.5h to remove impurities such as water vapor, hydrogen, carbon dioxide, nitrogen and organic components, and then sintered at 830°C for 1h, followed by vacuum sintering at 1150°C for 1.5h, and then kept at 1150°C for 1.5h;

[0095] Finally, the mixture was cooled to 60°C and kept for 3 minutes, then quickly heated to 900°C and kept for 1.5 hours, and then cooled to 600°C and kept for 1 hour to obtain a semi-finished product.

[0096] S5: Grinding: The semi-finished product is ground by electric spark wire cutting and centerless grinding. The magnet product obtained in this embodiment has a specification of φ10mm×5mm cylinder.

[0097] Example 4

[0098] The high coercive force magnet of this embodiment is different from that of the embodiment 3 in that: in step S2, the average particle size of the fine powder is 5 μm, and the rest is the same as that of the embodiment 3.

[0099] Example 5

[0100] The high coercive force magnet of this embodiment is different from that of the embodiment 3 in that: in step S2, the average particle size of the fine powder is 10 μm, and the rest is the same as that of the embodiment 3.

[0101] Example 6

[0102] The high coercive force magnet of this embodiment is different from that of Embodiment 5 in that among the raw materials, the auxiliary material is composed of metallocene and antioxidant in a molar ratio of 0.55:1, and the rest is the same as that of Embodiment 5.

[0103] Wherein, the metallocene is ferrocene and the antioxidant is tert-butylhydroquinone.

[0104] The preparation method of the high coercive force magnet of this embodiment is the same as that of Embodiment 5.

[0105] Example 7

[0106] The high coercive force magnet of this embodiment is different from that of Embodiment 5 in that among the raw materials, the auxiliary material is composed of metallocene and antioxidant in a molar ratio of 0.75:1, and the rest is the same as that of Embodiment 5.

[0107] The metallocene is dichlorotitanium cyclopentadienyl and the antioxidant is antimony dialkyl dithiocarbamate.

[0108] The preparation method of the high coercive force magnet of this embodiment is the same as that of Embodiment 5.

[0109] Example 8

[0110] The high coercive force magnet of this embodiment is different from that of Embodiment 5 in that among the raw materials, the auxiliary material is composed of metallocene and antioxidant in a molar ratio of 0.6:1, and the rest is the same as that of Embodiment 5.

[0111] The metallocene is dichlorotitanium cyclopentadienyl and the antioxidant is antimony dialkyl dithiocarbamate.

[0112] The preparation method of the high coercive force magnet of this embodiment is the same as that of Embodiment 5.

[0113] Example 9

[0114] The high coercive force magnet of this embodiment is different from that of Embodiment 5 in that among the raw materials, the auxiliary material is composed of metallocene and antioxidant in a molar ratio of 0.6:1, and the rest is the same as that of Embodiment 5.

[0115] The metallocene is composed of ferrocene and manganocene in a molar ratio of 1:0.5. The antioxidant is antimony dialkyl dithiocarbamate.

[0116] The preparation method of the high coercive force magnet of this embodiment is the same as that of Embodiment 5.

[0117] Example 10

[0118] The high coercive force magnet of this embodiment is different from that of Embodiment 5 in that among the raw materials, the auxiliary material is composed of metallocene and antioxidant in a molar ratio of 0.6:1, and the rest is the same as that of Embodiment 5.

[0119] The metallocene is composed of ferrocene and zirconium chloride in a molar ratio of 1:0.2, and the antioxidant is antimony dialkyl dithiocarbamate.

[0120] The preparation method of the high coercive force magnet of this embodiment is the same as that of Embodiment 5.

[0121] Embodiment 11

[0122] The high coercive force magnet of this embodiment is different from that of Embodiment 5 in that among the raw materials, the auxiliary material is composed of silicon carbide and antioxidant in a molar ratio of 0.6:1, and the rest is the same as that of Embodiment 5.

[0123] Wherein, the antioxidant is antimony dialkyl dithiocarbamate.

[0124] The preparation method of the high coercive force magnet of this embodiment is the same as that of Embodiment 5.

[0125] Example 12

[0126] The high coercive force magnet of this embodiment is different from that of Embodiment 5 in that among the raw materials, the auxiliary material is composed of dysprosium trioxide and antioxidant in a molar ratio of 0.6:1, and the rest is the same as that of Embodiment 5.

[0127] Wherein, the antioxidant is antimony dialkyl dithiocarbamate.

[0128] The preparation method of the high coercive force magnet of this embodiment is the same as that of Embodiment 5.

[0129] Comparative Example

[0130] Comparative Example 1

[0131] The high coercive force magnet of this comparative example includes the following components in percentage by mass: 27.5% of praseodymium-neodymium alloy, 1.2% of gadolinium-iron alloy, 1.5% of ferroboron alloy, 6% of cerium, 0.55% of copper, 0.5% of aluminum, 0.5% of zirconium, 0.15% of titanium, and 0.25% of cobalt; the remainder is iron and other inevitable impurities.

[0132] The preparation method of the high coercive force magnet of this comparative example is the same as that of Example 1.

[0133] Comparative Example 2

[0134] The high coercive force magnet of this comparative example is made of the following raw materials in parts by weight: 5.3 kg of material A, 0.26 kg of material B, and 0.055 kg of auxiliary materials.

[0135] Among them, material A includes the following components in percentage by mass: 15% praseodymium-neodymium alloy, 2% gadolinium-iron alloy, 0.5% ferroboron alloy, 12% cerium, 0.1% copper, 0.25% aluminum, 0.35% zirconium, 0.1% titanium, and 0.25% cobalt; the remainder is iron and other inevitable impurities.

[0136] Material B includes the following components in mass percentage: Al: 23.6%, Si: 0.35%, Cr: 0.1%; the remainder is iron and other inevitable impurities. The auxiliary material is boron carbide.

[0137] The preparation method of the high coercive force magnet of this comparative example is the same as that of Example 1.

[0138] Comparative Example 3

[0139] The high coercive force magnet of this comparative example is different from that of Example 1 in that the raw materials do not contain material B, and the rest are the same as those of Example 1.

[0140] Comparative Example 4

[0141] The high coercive force magnet of this comparative example is different from that of Example 1 in that the raw materials do not contain auxiliary materials, and the rest are the same as those of Example 1.

[0142] Comparative Example 5

[0143] The high coercive force magnet of this comparative example is different from that of Example 1 in that the average particle size of the material A and the material B in the raw materials is 25 μm, and the rest is the same as that of Example 1.

[0144] Performance testing

[0145] Detection Methods

[0146] The high coercive force magnets of Examples 1-12 and Comparative Examples 1-5 were tested in B. r 、(BH)max、H cj , the test results are shown in Table 1.

[0147] Table 1 High coercivity magnet performance test data of Examples 1-12 and Comparative Examples 1-5

[0148]

[0149]

[0150] By analyzing Examples 1-3 and Comparative Examples 1-2 and combining with Table 1, it can be seen that by using a two-component compound of material A and material B, the light and heavy elements in material B are used to penetrate and diffuse between the interfaces of the main phase crystals, so as to adjust the overall grain boundary energy, inhibit the growth of abnormal grains, refine the grains, and improve the coercive force of the magnet. It can be seen that compared with the conventional NdFeB magnet in Comparative Example 1, the coercive force of Example 3 is improved by about 9.2%.

[0151] Furthermore, analysis of Examples 1-3 and Comparative Example 2 shows that the M component in Material B further improves the coercive force of the magnet, with Example 1 improving by about 2% compared to Comparative Example 2. It is speculated that the addition of the M component causes the Nd-rich liquid in the magnet to melt the edges and irregular surface of the fine particles, thereby providing a better wrapping effect on the main phase crystals.

[0152] In addition, it can be seen from the analysis of Examples 1-3 and Comparative Examples 3-4 that when material B is not added, the performance of the magnet is greatly reduced. At the same time, it can be seen that the addition of auxiliary materials can reduce the oxidation degree of magnetic powder during the powder making process and reduce the generation of oxide impurities. In addition, during the sintering process, the auxiliary materials can play a certain role in densifying the magnet and surrounding the main phase grains to cut off the exchange coupling, further improving the coercive force of the magnet. It can be seen that the coercive force of Example 1 is increased by about 1.1% compared with Comparative Example 4.

[0153] It can be seen from the analysis of Examples 4-5 and Comparative Example 5 in combination with Table 1 that the particle size after pulverizing is optimized and adjusted to further reduce the generation of abnormal grains, thereby improving the overall performance of the magnet.

[0154] From the analysis of Examples 6-7, Examples 8-9, and Examples 10-12 and in combination with Table 1, it can be seen that optimizing and adjusting the type and ratio of metallocenes further improves the comprehensive performance of the magnet, especially when the metallocene is composed of ferrocene and manganocene, the coercive force is higher, and when the auxiliary material is composed of dysprosium trioxide and an antioxidant, the coercive force decreases by about 2.39% compared with Example 9. It is speculated that the addition of dysprosium trioxide may cause some elements to be freed outside the grain boundary phase, resulting in a decrease in the density and magnetic properties of the magnet.

[0155] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high coercive force magnet, characterized in that: The invention is prepared from the following raw materials in parts by weight: 53-68 parts of material A, 1.9-2.6 parts of material B, and 0.55-0.82 parts of auxiliary materials; The material A includes the following components in percentage by mass: Praseodymium-neodymium alloy 15-25.5%; Gadolinium iron alloy 1.5-2%; Boron iron alloy 0.5-1.2%; Cerium 7-12%; Copper 0.1-0.3%; Aluminum 0.25-0.5%; Zirconium 0.2-0.35%; Titanium 0.1-0.18%; Cobalt 0.25-0.45%; The balance is iron and other unavoidable impurities; The material B includes the following components in percentage by mass: M:23.6-30.2%; Si: 0.12-0.35%; Cr:0.1-0.25%; The balance is iron and other inevitable impurities; the M is at least one of Mn, In, Ag, Mg, Y, La, Ce, and Sc; The auxiliary material is composed of metallocene and antioxidant in a molar ratio of (0.55-0.75):1; The metallocene is at least one of ferrocene, manganocene, zirconium chloride, and titanium chloride; The antioxidant is one of tert-butylhydroquinone and antimony dialkyl dithiocarbamate.

2. A high coercive force magnet according to claim 1, characterized in that: The mass ratio of material A to material B is (20-41):

1.

3. The high coercive force magnet according to claim 1, characterized in that: The average particle size of the material A and the material B is 5-10 μm.

4. A method for preparing a high coercive force magnet as claimed in any one of claims 1 to 3, characterized in that: The steps include: S1: Smelting: according to the formula of material A, praseodymium-neodymium alloy, gadolinium-iron alloy, boron-iron alloy, cerium, copper, aluminum, zirconium, titanium, cobalt and the remaining components are measured and mixed evenly for smelting to obtain smelting material A; According to the formula of material B, M, Si, Cr and the remaining components are mixed evenly and smelted to obtain smelting material B; S2: Powder making: hydrogen-crushing the smelting material A and the smelting material B to obtain a coarse powder; then the coarse powder and the auxiliary materials are mixed together and jet-milled to obtain a fine powder; S3: Molding: The fine powder is filled, oriented and pressed in a mold to obtain a green body; S4: Sintering: Dehydrogenate, sinter and temper the green body to obtain a semi-finished product; S5: Grinding: The semi-finished product is obtained after grinding.

5. The method for preparing a high coercive force magnet according to claim 4, characterized in that: In step S4, the sintering is performed at 830-900°C in vacuum for 0.5-1h, followed by 1050-1150°C in vacuum for 1.5-2h, and then kept at 1150-1250°C for 1-1.5h.

6. The method for preparing a high coercive force magnet according to claim 4, characterized in that: In step S4, the tempering is performed by air cooling to 60-80°C and then maintaining the temperature for 1-3 minutes, then rapidly heating to 850-900°C and maintaining the temperature for 1.5-2 hours, and then cooling to 500-600°C and maintaining the temperature for 1-1.5 hours.

Citation Information

Patent Citations

  • NdFeB magnet and preparation method thereof

    CN104064301A

  • Rare earth permanent magnet produced by applying abundant rare earth cerium (Ce) and preparation method thereof

    CN103123839A